2018
DOI: 10.1029/2018gl079288
|View full text |Cite
|
Sign up to set email alerts
|

Induced Seismicity in Western Canada Linked to Tectonic Strain Rate: Implications for Regional Seismic Hazard

Abstract: A rapid increase of injection-induced earthquakes (IIE) is often linked to a higher level of seismic hazard. In this study, we compare the geodetically defined moment rate to seismicity distribution in western Canada where significant IIE are observed. The regional seismic pattern is dominated by IIE, both in number and moment, along a 150-km wide NW-SE band of moderate strain rate in the easternmost Cordillera and foothills. The observed rate of moment release from local earthquakes is much closer to the tect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 78 publications
2
55
0
Order By: Relevance
“…Based on our analysis, distance to the Cordilleran deformation front is one of the most important parameters affecting SAP. In part, this supports a model proposed by Kao et al (2018), who used sparse GPS data to show that the likelihood of induced seismicity in western Canada may be closely related to crustal strain rate. They identified a region in the foreland of the deformation front (Figure 3) that is characterized by both higher values of crustal strain rate and prevalence of induced seismicity.…”
Section: Discussionsupporting
confidence: 86%
“…Based on our analysis, distance to the Cordilleran deformation front is one of the most important parameters affecting SAP. In part, this supports a model proposed by Kao et al (2018), who used sparse GPS data to show that the likelihood of induced seismicity in western Canada may be closely related to crustal strain rate. They identified a region in the foreland of the deformation front (Figure 3) that is characterized by both higher values of crustal strain rate and prevalence of induced seismicity.…”
Section: Discussionsupporting
confidence: 86%
“…Although the selection of regions was based on the parameter b by the Kaltek method, which is more related to the nature of the earthquake, the constructed maps show that areas of increased risk of earthquakes correspond to the regions where the modern horizontal deformations are significant. Kao, et al, [2018] demonstrate correlations between crustal deformations and weak injection-induced earthquakes in Western Canada. To do this, the study area is divided into squares with sides of 20 km.…”
Section: Introductionmentioning
confidence: 83%
“…While the fundamental mechanisms for wastewater disposal-related seismicity are generally agreed upon, namely the diffusion of pore pressure promoting shear-failure along preexisting faults, the triggering processes of HF-induced seismicity remain less well understood. Fault reactivation may be attributable to several different sources, including hydraulic transmission between existing faults, new fractures and fluid injection wells (Galloway et al, 2018;Skoumal et al, 2018), fluid diffusion through semi-permeable rock causing pore pressure changes (Bao & Eaton, 2016), post-injection stress relaxation (Hajati et al, 2015), fluid-induced aseismic slip (Scuderi & Collettini, 2016;Scuderi et al, 2017;Bhattacharya & Viesca, 2019), fault maturity (Kozłowska et al, 2018;Brudzinski & Kozłowska, 2019), tectonic strain rates (Kao et al, 2018), and intra-cluster elastic stress redistribution and triggering of micro-seismicity (Stein, 1999;Sagiya et al, 2002;Maghsoudi et al, 2016Maghsoudi et al, , 2018. On the other hand, a recent study by Kettlety et al (2019) showed that elastic stress transfer may weakly promote failure initially during HF and later actually inhibit further slip.…”
Section: List Of Appendicesmentioning
confidence: 99%
“…The global rise in induced seismicity together with advancement in detection capability over the past decade has resulted in an abundance of earthquake data from which much new information is being gathered (Doglioni, 2018). Better understanding of tectonic strain rates, triggering mechanisms and geologic controls, updated hydrogeological models, and analyses of spatiotemporal clustering patterns and statistics have allowed for some improvements in the identification of induced activity and several adjustments to seismic hazard analysis (Llenos & Michael, 2013;Atkinson et al, 2016;Petersen et al, 2016;Zaliapin & Ben-Zion, 2016;Atkinson, 2017;Langevin et al, 2017;Schoenball & Ellsworth, 2017;Kao et al, 2018;Zhang et al, 2019). However, the wide-ranging and sometimes conflicting results attained across individual case studies (see Keranen & Weingarten, 2018) highlight the complex nature of induced seismic processes and illustrate the need for further investigation.…”
Section: Thesis Structurementioning
confidence: 99%